A newly described Lomatogonium madhmaheshwariansis is a synonym of Swertia alpina - Kumar, Aashish; Singh, Harsh (Phytotaxa, 2024)
Our critical examination of the plant collected from various glaciers of Uttarakhand Himalaya namely, Maitoli, Sunderdunga and Yumnotri during September 2021, including the type specimen and the protologue convinced us that the recently described Lomatogonium madhmaheshwariansis is not different from Swertia alpina and therefore, it should be synonymized with the latter. All the characters of S. alpina like leaves shape, inflorescence, flower colour, anther shape, capsule and seeds are similar as in case of L. madhmaheshwariansis.